PUSAT PERBELANJAAN BATIK DI YOGYAKARTA DENGAN PENDEKATAN ARSITEKTUR METAFORA - Haris Cahyo Nugraha; Agung Kumoro; Agus Heru Purnomo (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Increasing industrial development of a positive impact on economic growth in Indonesia. One of wich is a batik industry. This development requires the craftsmen to continue to enhance and improve its performance in order to continue to survive and even win the competition with a variety of other industries. Therefore we need a forum to facilitate the activities of the batik industry that are showcased as well sell. The design of batik shopping centre in Yogyakarta was motivated by many craftsmen batik in Yogyakarta, yet the presence of a special place that embodies batik exhibitions, as well as the location of batik product marketing that are still scattered making it difficult for consumers to visit the marketing area. Therefore we need a forum that concentrates in Yogyakarta batik products that reflect the character of batik. The purpose of the design is to create a physical container as a marketing and exhibition of batik in order to increase the value of batik domestic sales. The problem design is how to realize the characteristic of batik into the physical form of the building. The design methods used is metaphore architecture as a way to communicate the function of shopping centre building which has batik commodity inside. The approach chosen so that the characteristic and elements of metaphorical architecture of a batik can appear in the form of a building with an analogy of characteristic/ element on an object that is associated with batik. Key words:: Shopping Centre, Batik, metaphore architecture.